Determinasi Nilai Perusahan pada Sektor Manufaktur di Bursa Efek Indonesia - Isti Riana Dewi; Dewi Anggun Puspitarini; Ingrid Panjaitan (Esensi: Jurnal Bisnis dan Manajemen, 2021)
The condition of the decline in Indonesia's economic growth is different from the condition of the manufacturing industry that is getting better. the manufacturing industry has increased by 4.01% since 2016, supported by increased investment in certain industrial groups. This study aims to see the factors that affect the value of manufacturing companies in Indonesia. Retrieval by purposive sampling of 20 companies, using multiple linear regression analysis. There is a positive influence between institutional ownership, debt policy, and profitability on firm value, but not with dividend and interest rate policies. Investors need to pay attention to institutional ownership that indicates that the company is well managed. Besides, debt and profitability policies also need to be considered because for companies that are in debt, the prospects for expanding the company tend to be high, as well as if they have high profits.Cara Mengutip:Dewi, I. R., & Puspitarini, D. A. (2021). Determinasi Nilai Perusahaan Pada Sektor Manufaktur di Bursa Efek Indonesia. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.19329.